Where China meets India - "Myint-U, Thant" (London, 2011)
From their very beginnings, the civilizations of China and India have been walled off from each other, not only by the towering summits of the Himalayas, but also by the vast and impenetrable jungle, hostile tribes, and remote inland kingdoms that once stretched a thousand miles from Calcutta across Burma to the upper Yangtze River. In the next few years this last great frontier will likely vanish - forests cut down, dirt roads replaced by superhighways, insurgencies ended - leaving China and India exposed to each other as never before. This basic shift in geography is as profound as the opening of the Suez Canal. What will this change mean? Thant Myint-U is in a unique position to know. Over the past few years he has travelled extensively across this vast territory. In a region of long-forgotten kingdoms and modern-day wars, high-speed trains and gleaming new shopping malls have now come within striking distance of the last remaining forests and impoverished mountain communities. And he has pondered the new strategic centrality of Burma, the country of his ancestry, where Asia's two rising giant powers - China and India - appear to be vying for supremacy. Part travelogue, part history, part investigation, "Where China Meets India" takes us across the fast-changing Asian frontier, giving us a masterful account of the region's long and rich history and its sudden significance for the rest of the world.
Keywords: China-Foreign relations-India